Makna Denotasi dan Konotasi dalam Film "The Hundred-Foot Journey" (Kajian Semantik) - Yusti, Fatika; Prihandini, Asih (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
Research on “Denotative and Connotative Meanings in The Hundred-Foot Journey Movie (Semantic Study)” aims to identify references and meanings, with a focus on denotative and connotative meanings. The objective of the research is to understand the constructed meanings of cultural differences using Geoffrey Leech's theory (1981) in a semantic study approach. Conversational sentence data was taken from the film The Hundred-Foot Journey. The descriptive-qualitative method consists of the production of texts from verbal sources, text analysis, and interpretation to analyze data in discourse analysis. The findings show that meaning in speech is not limited to simple denotative meanings, but often develops into connotative meanings that are rich in cultural, emotional, and social power relations. The denotative and connotative meanings identified provide an understanding of each object or concept, resulting in an awareness of cultural differences in the communication process, especially in the dynamic interpretation of language Keywords: Denotation, Connotation, Culture, Film